Storms of my grandchildren the truth about the coming climate catastrophe and our last chance to save humanity - Hansen, James E. (James Edward) 1941- (Bloomsbury USA, 2011)
"In Storms of My Grandchildren, Dr. James Hansen--the nation's leading scientist on climate issues--speaks out for the first time with the full truth about global warming: The planet is hurtling even more rapidly than previously acknowledged to a climatic point of no return. Although the threat of human-caused climate change is now widely recognized, politicians have failed to connect policy with the science, responding instead with ineffectual remedies dictated by special interests. Hansen shows why President Obama's solution, cap-and-trade, which Al Gore signed on to, won't work; why we must phase out all coal; and why 350 parts per million of carbon dioxide in the atmosphere is a goal we must achieve if our children and grandchildren are to avoid global meltdown and the horrific storms of the book's title."--Back cover, page 2.